Zmowa nauki. Strach przed technologią we współczesnych amerykańskich teoriach spiskowych - Różycki, Michał (Er(r)go. Teoria - Literatura - Kultura, 2014)
Michał Różycki Conspiracy of Science. Technophobia in Contemporary American Conspiracy Theories The goal of the paper is to outline the notion of the fear of technology and mistrust of the scientific establishment present in 21st century American conspiracy theories. It argues that such negative connotations are invariably tied to the so-called New World Order (NWO) conspiracy theory. The text opens with a brief outline of the origins of the belief in the NWO, starting with the late 18th century theories about the Bavarian Illuminati, and culminating with the influence of the Cold War mentality. What the fear of technology stands for in conspiracy theory narratives, the text argues, is the fear of the loss of personal agency. This loss is caused by overreliance on technology which is controlled by a nefarious conspiracy. The text relies on primary sources in the form of works of an American conspiracy theorist, radio host and political activist, Alex Jones.